2022
DOI: 10.3928/01913913-20220817-01
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Factors Impacting the Viability of Pediatric Ophthalmology

Abstract: Purpose: To create a survey that assesses the economic factors impacting the viability of pediatric ophthalmology between January 2021 and July 2022. Methods: A 12-question survey was distributed to United States–based pediatric ophthalmologists on the American Association for Pediatric Ophthalmology and Strabismus discussion board and various social media fora. Demographic, economic, and workforce pattern data were collected and analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Previous reports support our findings of resident preferences towards certain components of the ophthalmic examination [3] . The least likeable components in our study were gonioscopy, ocular motility testing and visual acuity testing.…”
Section: Perception Of the Ophthalmic Examinationsupporting
confidence: 92%
“…Previous reports support our findings of resident preferences towards certain components of the ophthalmic examination [3] . The least likeable components in our study were gonioscopy, ocular motility testing and visual acuity testing.…”
Section: Perception Of the Ophthalmic Examinationsupporting
confidence: 92%
“…These findings are concerning given that the United States is currently facing an overall pediatric ophthalmology workforce crisis, i.e., severely impacting access to eye care. [20][21][22] We hypothesize that this may further reflect each health care system's familiarity with the insurance type they predominately accept, and conversely, each patient's familiarity with the health care system that most commonly accommodates their insurance. For example, the phone system, appointment scheduling process, and on-line/mobile application patient portals are distinct between the two hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A survey among pediatric ophthalmologists assessed the economic challenges they faced during COVID-19. 63 It showed that 65.1% met a decrease in revenue from OPD greater than 10%, and another 64.3% agreed to a more than 10% decrease in surgical revenue. 20.9% of pediatric ophthalmologists were forced to plan premature retirement because of COVID-19.…”
Section: Impact On Pediatric Ophthalmologistsmentioning
confidence: 97%